Function rules : a Swedish approach to design glamour. - Pagold, Susanne, ....- (Stockholm : Arvinius, 2006)
This book is about adapting the world of things to humans. It is also the first study of successful Swedish design- and development firm Ergonomidesign. Featuring essays, interviews and case stories, this beautifully illustrated volume puts Ergonomidesign's achievements in a societal perspective, that goes way beyond bad backs and ugly office chairs. The case studies document research methods and the development of new design solutions which are based on users' needs. The interviews offer insights into the thought processes of the designers, and the essays provide a critical vision of ergonomic design in today's world.This group of designers has an impressive record of creating best-selling object which are functional, inclusive, sustainable - and sometimes even fashionable.
Keywords: Ontwerpen